2006
DOI: 10.1080/02640410500249399
|View full text |Cite
|
Sign up to set email alerts
|

Influence of caffeine on perception of effort, metabolism and exercise performance following a high-fat meal

Abstract: This study examined the effects of caffeine, co-ingested with a high fat meal, on perceptual and metabolic responses during incremental (Experiment 1) and endurance (Experiment 2) exercise performance. Trained participants performed three constant-load cycling tests at approximately 73% of maximal oxygen uptake (VO2max) for 30 min at 20 degrees C (Experiment 1, n = 8) and to the limit of tolerance at 10 degrees C (Experiment 2, n = 10). The 30 min constant-load exercise in Experiment 1 was followed by incremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 40 publications
4
14
1
Order By: Relevance
“…In this study, athletes presented higher values of glycemia with the ingestion of the CSD compared to the CCD, thus agreeing with the results obtained in other studies (Hadjicharalambous et al, 2006;Woolf, Bidwell, & Carlson, 2008), suggesting a lower glucose utilization during exercise in athletes consuming caffeine. Another proposed mechanism is the increase of sympathetic nervous system activity by caffeine, which promotes secretion of adrenaline and noradrenaline (Davis et al, 2003;Yeo, Jentjens, Wallis, & Jeukendrup, 2005).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this study, athletes presented higher values of glycemia with the ingestion of the CSD compared to the CCD, thus agreeing with the results obtained in other studies (Hadjicharalambous et al, 2006;Woolf, Bidwell, & Carlson, 2008), suggesting a lower glucose utilization during exercise in athletes consuming caffeine. Another proposed mechanism is the increase of sympathetic nervous system activity by caffeine, which promotes secretion of adrenaline and noradrenaline (Davis et al, 2003;Yeo, Jentjens, Wallis, & Jeukendrup, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…These studies have shown that during exercise, caffeine acts on blood glycemia, increasing its concentration in both aerobic (Hadjicharalambous, Georgiades, Kilduff, Turner, Tsofliou, Pitsiladis et al, 2006) and anaerobic exercise (Woolf, Bidwell & Carlson, 2008). Other researchers have also shown that caffeine tends of promote an increase in plasma lactate (Carr, Dawson, Schneiker, Goodman, & Lay, 2008) (Bassini-Cameron, Sweet, Bottino, Bittar, Veiga et al, 2007) and FFA (McNaughton et al, 2008), while K + generally suffers a decrease after its ingestion (Simmonds, Minahan, & Sabapathy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in, or dysregulation of, central mechanisms that modulate or regulate activity may occur with aging (14,41,45). Alternatively, there may be a change in the central perception of fatigue, resulting in a lower threshold for activity cessation (2,12,31,42). There may be dysfunction or dysregulation in peripheral neurons or intrinsic muscle function limiting the activity that a subject may be able to perform.…”
Section: Discussionmentioning
confidence: 99%
“…BMR was measured on three consecutive mornings (days 12,13,14) between 0600 and 0800 in the subjects who had slept uninterrupted the previous nights in the GCRC (subjects were admitted to the GCRC on the evening of day 11). Subjects were not moved prior to measurements and had not eaten since 2100 the night before.…”
Section: Weight Maintenance Dietary Provisionmentioning
confidence: 99%
“…1,2 It gives the perception of decreased intoxication without altering impairment. 1,3,4 Previously a do-it-yourself activity by college students, 5 entrepreneurs made it easier for underage individuals by producing premixed drinks, such as Rock Star 21, Joose, 6 and Steel Reserve, 6 -9 usually by adding vodka, with an alcohol content of 6% to 9.9%, and caffeine (80 to 400 mg) to the energy drink. 6 -9 When asked to speak on this topic to a parents' group, I was uneducated.…”
mentioning
confidence: 99%